2010
DOI: 10.1177/1087054710381481
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Gender Gap in Referrals for Children With ADHD and Other Disruptive Behavior Disorders

Abstract: The current study adds to previous literature on gender bias in ADHD referrals by providing evidence for the differential referral of ADHD boys and girls to treatment based on presentation of symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 30 publications
2
30
0
1
Order By: Relevance
“…Additional study content not extracted for this review included attitudes towards interventions for other disorders, measures of ADHD knowledge and measures of educators' experience of interventions. Nineteen [214][215][216][217]222,223,[225][226][227][228][229]233,236,239,240,242,243,246 of the studies used vignettes, meaning that participants read a case description of a child displaying ADHD symptoms and then indicated their beliefs regarding intervention(s) to be used for that case. 214,217,[222][223][224][225][226][227][228][229][233][234][235][236][237][240][241][242][244][245][246][247][248] ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional study content not extracted for this review included attitudes towards interventions for other disorders, measures of ADHD knowledge and measures of educators' experience of interventions. Nineteen [214][215][216][217]222,223,[225][226][227][228][229]233,236,239,240,242,243,246 of the studies used vignettes, meaning that participants read a case description of a child displaying ADHD symptoms and then indicated their beliefs regarding intervention(s) to be used for that case. 214,217,[222][223][224][225][226][227][228][229][233][234][235][236][237][240][241][242][244][245][246][247][248] ).…”
Section: Resultsmentioning
confidence: 99%
“…Where data were missing that would allow reviewers to convert reported attitude statistics into percentages for each intervention studied, or there was a lack of detail regarding measures used, authors were contacted. [214][215][216][217] Only Kos replied with a copy of the scale used in that study. 216 …”
Section: Data Extractionmentioning
confidence: 99%
“…It has been argued that the more common hyperactivity symptoms in boys, with a higher co-morbidity of disruptive behaviors (Gershon, 2002;Taurines et al, 2010), evoke more attention in the classroom situation (Rucklidge, 2010). The finding may also partially explain the previous findings of a higher boy/girl ratio in clinical samples, as compared with the adult population samples (Coles, Slavec, Bernstein, & Baroni, 2012;Nussbaum, 2012); referrals to psychiatric services during childhood are often initiated by the teachers, while such contacts are often self-initiated in adulthood. Although this study was not designed to evaluate bias in the referral process, the effect of the child's gender on teacher ratings is notwithstanding of interest, given that the entire sample had been clinically assessed and diagnosed with ADHD/ADD, and hence the signs of clinically significant impairment were present not only at home but also in the school settings.…”
Section: Discussionmentioning
confidence: 95%
“…For example, Demetriou, Wilson, and Winterbottom (2009) found that female teachers had a tendency to more frequently send male students off to special units instead of providing for them in the general classroom. The high frequency of boys diagnosed with AS, and the discrepancy in male and female teachers' approaches is likely to have an impact on provision (Abikoff, Jensen, & Arnold, 2002;Coles et al, 2012). Due to the fact that impairments in social skills become more prominent at higher levels, differences between teachers' perceptions in kindergarten and secondary school have been noted (Batten, 2005;Humphrey & Lewis, 2008;Myles, 2003).…”
Section: The Role Of Teachersmentioning
confidence: 99%
“…Since 72% of the teacher population is women in Sweden (SALAR, 2010) differences between male and female teachers have important implication for practice (Haase 2008). Research has shown that male teachers in general are much less likely to refer students with different kinds of problematic behavior to special education units, instead attempting to support them in the general classroom (Abikoff et al, 2002;Coles et al, 2012;McIntyre, 1990). We found that male teachers tended to be more concerned with adapting educational the environment which indicates that students might miss out on accommodation of the school environment to a certain extent.…”
Section: Teachers -The Subjects Of the Investigation Of Srsmentioning
confidence: 99%